Pengaruh Karakteristik Chief Excecutive Officer Terhadap Financial Leverage - Aisah, Putri; Purwaningsih, Eny (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The food and beverage manufacturing sector is growing rapidly, marked by many business innovations and new products. The decision to use debt is important to balance return and risk expectations. Corporate governance includes business financing decisions, including the role of the CEO in financial leverage. This study examines the effect of CEO characteristics on corporate leverage in food and beverage manufacturing entities listed on the Indonesia Stock Exchange for the 2020-2023 period. Using causal and purposive sampling methods, 116 data were obtained from 29 entities. The results of the study show that age, CEO experience, educational background, CEO gender, and company size simultaneously affect leverage. Partially, CEO age, CEO experience, and company size have a positive effect on leverage, while CEO education and gender do not have a significant effect. The t value and significance level indicate that experience and organizational scale are more decisive in determining strategic debt management decisions. Meanwhile, CEO education and gender, as demographic factors, do not play a major role in the company's financial leverage. Keywords: CEO Gender, CEO Education, Company Size, Financial Leverage, Job Experience